In situ construction of hierarchical core–shell Fe3O4@C nanoparticles–helical carbon nanocoil hybrid composites for highly efficient electromagnetic wave absorption. (January 2021) - Zhao, Yongpeng; Zhang, Hao; Yang, Xuan; Huang, Hui; Zhao, Guolin; Cong, Tianze; Zuo, Xueqing; fan, Zeng; Yang, Shuaitao; Pan, Lujun
Abstract: Highly efficient microwave absorption materials with tunable electromagnetic properties have been attracting extensive attention. However, it still remains a challenge to fabricate the chiral materials decorated with core-shell structured magnetic-particles for excellent microwave absorption performance. Herein, a novel composite of helical carbon nanocoils (CNCs) and Fe3 O4 @C core-shell structures are synthesized, for the first time, via sequential processes of chemical vapor deposition (CVD) technique and hydrothermal reactions. By controlling the reaction temperature and time in CVD process, the composites with different morphologies and multilevel heterostructural interfaces are obtained. The minimum reflection loss of the CNC/Fe3 O4 @C composite reaches −47.5 dB at 13.4 GHz with a thickness of only 1.7 mm. Meanwhile, the composite also exhibits an effective frequency range (≤−10 dB) of as wide as 5.03 GHz at a thickness of only 1.5 mm. Our designs not only provide a scalable way for preparing a kind of novel and robust absorber but also offer inspirations for construction of a kind of composite consisting of chiral and core-shell structured materials. Graphical abstract: Image 1 Highlights: A novel composite of helical carbon nanocoils and Fe3 O4 @C core-shell structures with tunable electromagnetic properties are synthesized. The minimum reflection loss of the CNC/Fe3 O4 @C composite reaches −47.5 dB with a thickness of only 1.7 mm. Our designs offer inspirations for construction of a kind of composite consisting of chiral and core-shell materials.